1966
DOI: 10.1029/jz071i002p00495
|View full text |Cite
|
Sign up to set email alerts
|

A reconnaissance geophysical survey in the Andaman Sea and across the Andaman-Nicobar Island Arc

Abstract: A marine geophysical study of the Andaman Sea has been conducted as part of the International Indian Ocean Expedition. A combination of magnetic, gravity, bathymetric, and sea‐floor heat‐flux measurements, seismic sparker reflection profiles, and bottom sediment samples has been used in a study of the seaward continuity of major subaerial tectonic trends. The data indicate positive continuity of the structural trend of the Barisan Range of northern Sumatra and the Burma Range. It was found that the central gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1974
1974
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…The Andaman and Nicobar Islands stand on the outer ridge. Marine-geophysical studies of the system have been reported by ;Peter, Weeks, and Burns (1966);and Weeks, Harrison, and Peter (1967). Reflection profiles are given here in figures 21 and 30.…”
Section: Andaman-nicobar Arc and Andaman Seamentioning
confidence: 99%
See 1 more Smart Citation
“…The Andaman and Nicobar Islands stand on the outer ridge. Marine-geophysical studies of the system have been reported by ;Peter, Weeks, and Burns (1966);and Weeks, Harrison, and Peter (1967). Reflection profiles are given here in figures 21 and 30.…”
Section: Andaman-nicobar Arc and Andaman Seamentioning
confidence: 99%
“…The rift trends to sea at the opposite end of Sumatra also. Peter, Weeks, and Burns (1966) inferred from their widely spaced bathymetric traverses that the fault swings to a northward strike and continues along the submarine volcanic arc east of the Andaman-Nicobar outer ridge.…”
Section: Strike-slip Faultingmentioning
confidence: 99%
“…This region is still tectonically active, as evidenced by the several earthquakes of magnitudes in excess of 8 on the Richter scale and the intense vertical movements of the islands and sea mounts witnessed here over the past about 200 years (Bilham et al, 2005). It is generally accepted now that the Andaman sea is actively spreading along the transform faults with predominantly a strike-slip motion, where as most of the thrusting is observed to occur to the immediate west of the ANR (Curray et al,1982 andPeter et al, 1966). Peter et al (1966) observe from the marine gravity, magnetic and seismic studies that most of the tectonic elements in the Andaman region extend in to the Burmese as well as the Indonesian arcs.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted now that the Andaman sea is actively spreading along the transform faults with predominantly a strike-slip motion, where as most of the thrusting is observed to occur to the immediate west of the ANR (Curray et al,1982 andPeter et al, 1966). Peter et al (1966) observe from the marine gravity, magnetic and seismic studies that most of the tectonic elements in the Andaman region extend in to the Burmese as well as the Indonesian arcs. The ANR is the outer sedimentary arc, paralleling the inner igneous arc, which passes through the Barren and Narcondam islands in the NE Indian ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Results of the International Indian Ocean Expedition data conclusively prove that the Barren and Narcondam Islands, along with the invisible Bank, form the western fringe of the inner volcanic arc. This is also borne out by the results of seismic reflection, magnetic and gravity data in the Andaman Sea (Peter et al, 1966;Curray et al, 1982). These islands are arranged in echelon, more or less subparallel to the axis of the sea floor spreading, and are displaced by a complex system of transcurrent faults.…”
Section: Introductionmentioning
confidence: 99%